Business Model Innovation for Circular Economy in Fashion Industry: A Startups' Perspective - Ostermann, Cristina M.; Nascimento, Leandro da Silva; Zen, Aurora Carneiro (Frontiers in Sustainability, 2021)
Circular Economy (CE) has emerged as a potential strategy for developing business practices based on sustainability concerns, especially in the fashion industry, that presents high environmental and social impacts. Startups are responsible for introducing innovations in business conduction towards CE. As a current theme, research on Business Model Innovation for Circular Economy (BMI4CEs) has increased. However, empirical research in the fashion industry and startups is still scarce. This paper aimed to identify the key elements of startups’ BMI4CEs in the fashion industry. We conducted an exploratory and descriptive multi-case study composed of ten early-stage fashion startups from North America, Asia, and Europe. The sustainability’s environmental and economic dimensions receive priority in the analyzed BMI4CEs. On business type, it was found differences between product-based and service-based Business Models (BMs). The BMIs were based mainly on CE principles of closed-loop and reducing material use and consumption . BMs focus on CE strategies of product reuse and extend resource time by reducing consumption and material use. The proposed solutions are aligned with the closed-loop value creation strategy and focus on value retention at the material level. We developed four propositions for fashion startups to advance their CE contribution from a triple bottom line perspective. his research is based on empirical data and highlights new theoretical perspectives under an investigation area still little explored in the literature. Results enable fashion startup managers to better understand the functioning of BMI4CEs and the critical elements needed for their effectiveness.